Entrepreneurship Competence, and Innovation Bandung City Culinary SMES Performance Mediated By Knowledge Management - Aam Rachmat Mulyana; Mochamad Vrans Romi (International Journal of Economics (IJEC), 2023)
The purpose of this study was to determine Entrepreneurship Competency variables and Innovation variables that affect MSME Performance with Knowledge Management as a mediating variable. Entrepreneurship Competence latent variable (X1) (Strategic Competencies, Opportunity Competencies Relationship competencies, Conceptual Competencies, Organizing Competencies, Commitment Competencies, and Innovation (Innovation in Process, Innovation in Structure, Innovation in Culture, Innovation in HR) contributes an influence of 0.748 or 74.8% on MSME performance (Y2) mediated by knowledge management (Y1) while the remaining 25.2% is the influence of other factors that are not observed Knowledge management is a mediating variable while the dependent variable is MSME performance The sample method used used was a purposive sample with a sample size of 200 MSME owners.This study used the Equation Model Structural equation model with the help of Smart PLS 3. This research method is quantitative, namely conducting a primary data search with the research object of MSME owners registered at PT. LEN's UKM Fostering. Based on the results of the research partially the variables that have a significant effect are Entrepreneurship Competence, Innovation and Knowledge Management while Entrepreneurship Competence and Innovation on the performance of Culinary MSMEs in Bandung City which are mediated by Knowledge Management do not have a significant effect and give an effect with the nature of mediation which weakens, and reduces Entrepreneurship competence and Innovation.